Vakıf Kurucusu Olarak Osmanlı Esnafı (18. Yüzyıl İstanbul Örneği) - Koyuncu Kaya, Miyase (Vakıflar Genel Müdürlüğü, 2014)
Osmanlı şehirlerinde iktisadi faaliyetleri yürüten en önemli figür olan esnafın vakıflarla doğrudan veya dolaylı ilişkileri vardı. Osmanlı esnafı genellikle vakıfların kiracısı olarak mesleklerini icra etmekteydi. Bu çalışmada esnaf, vakıflarla ilişkisinde farklı bir kimlikle yani vakıf kurucusu olarak ele alınmıştır. Esnafın bireysel olarak vakıf kurma eğilimleri ve amaçları, Vakıflar Genel Müdürlüğü Arşivinde yer alan 18. yüzyıl İstanbul esnafına ait vakfiyeler çerçevesinde irdelenmiştir. 18. yüzyıl İstanbul örneğinde Osmanlı esnafının vakıf olarak kimlikleri, neleri vakfettikleri, aileleri, meslektaşlarıyla ilişkileri, vakıf şartları oluştururken yaptıkları tercihler ve beklentileri de analiz edilmiştir.

The artisans who were the most important figure carrying out economic activities in Ottoman cities had direct or indirect relations with waqfs. The artisans were usually tenants of waqf shops. In this study, the Ottoman artisans has been examined in a different way by looking at them as founder of waqfs. By using the waqfiyyes of artisans of 18th century Istanbul kept in Archives of Directorate General of Foundations, their intentions and aims to establish waqfs individually are searched in detail. By taking artisans of 18th century Istanbul as examples, their identities, their families, affiliations with their colleagues, the reasons why they tended to found waqfs, what they donated, what they expected have been analyzed.
Ottoman Artisans as Waqf’s Founders (18th Century Istanbul)
Keywords: Esnaf; Vakıf; İstanbul; Osmanlı; 18. yüzyıl; Artisans; Waqf; Ottoman; 18th century; Istanbul